2020
DOI: 10.1021/acs.langmuir.0c02539
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Behavior of Polyaniline on Carbon Nanofibers by Oxidative Chemical Vapor Deposition

Abstract: Oxidative chemical vapor deposition (oCVD) offers unique advantages as a liquid-free processing technique in synthesizing and integrating conducting polymers, including polyaniline (PANI), by enabling conformal coatings onto nanostructured substrates, like carbon nanofibers. With relatively thick nanofiber mats, the challenge is to ensure uniform coating thickness through the porous substrates. Here, the substrate temperature during oCVD is found to be a primary factor influencing PANI coating uniformity. Coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
6
0
1
Order By: Relevance
“…Considering that the SbCl 5 flow rate is the limiting factor of the oCVD process in the conditions tested as previously demonstrated, this behavior may be due to the low and decreasing SbCl 5 concentration existing near the heated substrate with increasing T sub . This is in agreement with the results of Li et al [30] who found for the oCVD of PANI from aniline and SbCl 5 that the process is most likely limited by reactant adsorption on the substrate surface because higher temperatures generally reduce vapor-to-surface adsorption (or sticking coefficient) and, therefore, reduce the amount of reactant at a surface available for reaction. T sub has no clear influence on the film uniformity as shown in Figure S5 of Supplementary Materials.…”
Section: Influence Of the Substrate Temperaturesupporting
confidence: 93%
“…Considering that the SbCl 5 flow rate is the limiting factor of the oCVD process in the conditions tested as previously demonstrated, this behavior may be due to the low and decreasing SbCl 5 concentration existing near the heated substrate with increasing T sub . This is in agreement with the results of Li et al [30] who found for the oCVD of PANI from aniline and SbCl 5 that the process is most likely limited by reactant adsorption on the substrate surface because higher temperatures generally reduce vapor-to-surface adsorption (or sticking coefficient) and, therefore, reduce the amount of reactant at a surface available for reaction. T sub has no clear influence on the film uniformity as shown in Figure S5 of Supplementary Materials.…”
Section: Influence Of the Substrate Temperaturesupporting
confidence: 93%
“…For nonporous oCVD PANI, uniform penetration into the full depth of the mat was achieved at high oCVD substrate temperatures, where the rate-limiting step is the adsorption of reactive vapors to the substrate. 19 Conformal coverage of free-standing silicon carbon nanowires by oCVD PEDOT provided an areal capacitance of 0.026 F/cm 2 at 0.2 mA/cm 2 , a factor of 3.7× over the unmodified nanowires. 20 The device retained nearly full capacity after 10,000 cycling events.…”
Section: Electrochemical Devicesmentioning
confidence: 98%
“…Supercapacitors were fabricated by the conformal coating of electrospun carbon nanofiber mats with porous oCVD PANI ( Figure 4 ). 18 The pores, ~40 nm in diameter, facilitated ionic transport. The resulting composite electrode had a specific capacitance of 149 F/g.…”
Section: Electrochemical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…187 Polyaniline (PANI) was conformally coated on carbon nanotubes via oCVD at a low deposition temperature. 82 Twolayer hybrid nano-and mesotubes were fabricated by deposition polymerization of PPX and metal on degradable template polymer fibers (PLA, poly(L-lactide)) via subsequent CVD. 104 A hybrid nanocomposite with graphene, dopamine, and PPY was fabricated for flexible supercapacitor electrodes by coating PPY on dopamine-loaded graphene.…”
Section: Polymer Compartmentalization and Compositesmentioning
confidence: 99%